Pilot Study of a Screen-Free Week: Exploration of Changes in Parent and Child Screen Time, Parent Well-Being and Attitudes, and Parent-Child Relationship Quality - Brandon T. McDaniel; Sydney Rasmussen; Lauren Reining; Leesha Culp; Kacey Deverell (Human Behavior and Emerging Technologies, 2023)
Screen use is associated with a variety of potential impacts on child development, which has led to recommendations to regulate screen use. The current pilot study was conducted to explore the potential effects of implementing screen-free times (Screen-Free Week) on parent and child screen use, parent feelings and well-being, and parent-child interactions and relationships. Specifically, we evaluated the outcomes utilizing pre and postintervention self-report surveys with 24 parents (of a child age 5 years or younger). Overall, the screen-free week program decreased parent depressive symptoms, increased the parenting of child screen time and establishments of screen time limits, and decreased both parent and child screen time. Though the decrease in overall parent and child screen time was not maintained by 4 weeks after, effects on parent depression, child TV watching, and parent phone use specifically during child time were maintained. These findings support previous research emphasizing screen-free times as a viable method to increase intentionality around screen use. Interestingly, the program appears to have had the strongest effects on parent phone use around their child, suggesting the program may build awareness in parents and may cause them to change or desire to change their screen habits during family time. Although we saw initial shifts in parent-child play, effects were not maintained by week 4. Yet, the small changes parents made across one week were not sufficient to shift the overall parent-child relationship. While effects cannot be viewed as definitive, it is promising that shifts were seen in parent well-being and screen use for a relatively small amount of effort across one week.